(untitled) (Research, Society and Development, 2021)
The upper labial frenum is a triangular anatomical structure that undergoes changes of shape, function and position during the development of the child. A displacement to the most apical portion about 3 to 4 mm above the marginal gingiva is expected. When this does not occur, with the frenum inserted in the incisive papilla, a developmental anomaly called the persistent tectolabial frenum is characterized. The timing and type of intervention in these situations generate much controversy; the evaluation of factors such as low insertion in the alveolar ridge, presence or absence of palatine papilla ischemia when the brake is pulled, presence of interincisive diastema, difficulty in hygiene and / or feeding and gingival retraction aid in the treatment decision. Thus, the objective of this study was to present 8 clinical cases on upper lip frenum approaches, discussing different moments. Children of different ages were evaluated and submitted to the following behaviors: frenectomy, repositioning by the Chelotti technique or clinical follow-up for later reevaluation. It was concluded that, although there is a frequent indication of intervention only after eruption of the permanent upper canines, there are other situations in which an early approach can bring more benefits to the patient.